2017
DOI: 10.1093/pasj/psx123
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic magnetism in centimeter- and meter-wavelength radio astronomy

Abstract: Magnetic field is ubiquitous in the Universe and it plays essential roles in various astrophysical phenomena, yet its real origin and evolution are poorly known. This article reviews current understanding of magnetic fields in the interstellar medium, the Milky Way Galaxy, external galaxies, active galactic nuclei, clusters of galaxies, and the cosmic web. Particularly, the review concentrates on the achievements that have been provided by centimeter and meter wavelength radio observations. The article also in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 491 publications
(521 reference statements)
0
26
0
Order By: Relevance
“…Large scale mappings of Faraday rotation measure (RM) of extragalactic linearly polarized radio sources have been achieved extensively in the decades (Taylor et al 2009;Oppermann et al 2012), with which various analyses have been obtained to investigate structures of galactic as well as intergalactic magnetic fields (e.g., review by Akahori et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Large scale mappings of Faraday rotation measure (RM) of extragalactic linearly polarized radio sources have been achieved extensively in the decades (Taylor et al 2009;Oppermann et al 2012), with which various analyses have been obtained to investigate structures of galactic as well as intergalactic magnetic fields (e.g., review by Akahori et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Quite on the contrary, several may contribute either simultaneously or sequentially, sympatrically or allopatrically, to the magnetization of the IGM 1 . Disentangling their respective contributions may become possible in the near future thanks to synchrotron measurements and Faraday tomography (e.g., [77,78])-especially when compared to numerical simulations that are able to track the various contributions [79,80]-or even in the statistical properties of the neutral gas during the epoch of reionization [81,82]. 1 Among the possible contributions is the resistive mechanism suggested in [76], in which temperature inhomogeneities of the IGM are responsible for spatial variations of the resistivity that induce rotational electric fields thanks to cosmic ray driven return currents.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of magnetic fields in galaxies can be classified based on its dominant mode: Axis-Symmetric Spiral (ASS, m = 0), Bi-Symmetric Spiral (BSS, m = 1), and Quadri-Symmetric Spiral (QSS, m = 2) types [2]. The azimuthal changes of RM can be used to classify the morphology and to solve the 180 • -ambiguity [2].…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of magnetic fields in galaxies can be classified based on its dominant mode: Axis-Symmetric Spiral (ASS, m = 0), Bi-Symmetric Spiral (BSS, m = 1), and Quadri-Symmetric Spiral (QSS, m = 2) types [2]. The azimuthal changes of RM can be used to classify the morphology and to solve the 180 • -ambiguity [2]. Former works have shown that IC342 and M31, for example, are classified into ASS [3,4] and that M81, M33 and NGC 6946 are classified into BSS [5,6] by examining azimuthal changes of RM.…”
Section: Introductionmentioning
confidence: 99%